Teaching with Love and Commitment: The Instructional Practices of African American Facilitators Engaged in Prevention Science Programs - Tracy N. Anderson (Adult Education Research Conference, 2009)
This paper reports the finding and conclusions of a study on how culture impacts the instructional practices of facilitators in nonformal settings.